Junctions in DNA: underexplored targets for therapeutic intervention - Ivens, Eleanor; Cominetti, Marco M.D.; Searcey, Mark (Bioorganic & medicinal chemistry, 2022)
[Display omitted] DNA has been a key target for cancer therapy, with a range of compounds able to bind and either impair its processing or induce damage. Targeting DNA with small molecules in a truly sequence specific way, to impair gene specific processes, remains out of reach. The ability of DNA to assume different structures from the classical double helix allows access to more specific ligand binding modes and, potentially, to new avenues of treatment. In this review, we illustrate the small molecules that have been reported to bind to three- and four-way junctions.